2016
DOI: 10.1016/j.drugalcdep.2016.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity as a protective factor for hazardous drinking and drug use among sexual minority and heterosexual women: Findings from the National Alcohol Survey

Abstract: Objective Despite research documenting disparities in risk for alcohol-related problems among sexual minority women, few studies explore potential protective factors within this population. This study examines how religiosity may function as a protective or risk factor for alcohol-problems or other substance use among sexual minorities compared to heterosexuals. Method Data from 11,169 women who responded to sexual identity and sexual behavior questions from three population-based National Alcohol Survey wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 55 publications
2
22
1
3
Order By: Relevance
“…In contrast to findings from a recent study of the protective effect of religiosity among SMW in the National Alcohol Survey (Drabble et al, 2016), we found no evidence of a protective effect for religiosity in relation to hazardous drinking, drug use, or depression in the full sample. The absence of a protective effect for religiosity among SMW has also been found in studies of young adults (Rostosky et al, 2007; Rostosky et al, 2010), and underscores the need for additional research about the role of religion and spirituality in health behaviors and mental health among diverse populations of SMW.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to findings from a recent study of the protective effect of religiosity among SMW in the National Alcohol Survey (Drabble et al, 2016), we found no evidence of a protective effect for religiosity in relation to hazardous drinking, drug use, or depression in the full sample. The absence of a protective effect for religiosity among SMW has also been found in studies of young adults (Rostosky et al, 2007; Rostosky et al, 2010), and underscores the need for additional research about the role of religion and spirituality in health behaviors and mental health among diverse populations of SMW.…”
Section: Discussioncontrasting
confidence: 99%
“…Findings from a recent study examining protective effects of religiosity among women by sexual identity suggested that higher levels of religiosity were protective against hazardous drinking and drug use among both sexual minority and heterosexual women (Drabble, Trocki, & Klinger, 2016). However, this study had a number of limitations including a small sample of SMW, absence of measures of spirituality, and insufficient power to explore possible differences by race/ethnicity.…”
Section: Introductionmentioning
confidence: 99%
“…Faith protects both women and men against substance abuse. A study of over 11,000 women, aged 18 and older, found significant reductions in alcohol and drug use by more religiously active women, including lesbian and bisexual women (Drabble et al 2016). Acheampong et al (2016) showed that women and men who use prescription opioids and who are actively religious and spiritual are less likely to engage in simultaneous polysubstance use (SPU).…”
Section: Sections Of the Studymentioning
confidence: 99%
“…There was been very little quantitative research examining the association between religion and substance use among SMW. In one exception, Drabble and colleagues [130] examined data from a large sample of US women who participated in one of three population-based National Alcohol Surveys (2000,2005,2010). Religiosity (the importance of religion in one's life) was significantly greater among exclusively heterosexual women than among lesbian or bisexual women or heterosexual women who reported same-sex sexual experience.…”
Section: Plos Onementioning
confidence: 99%
“…There is a need to more systematically examine similarities and differences in factors, such as marriage, that are typically identified as protective against hazardous drinking and drug use among heterosexual women. For example, although affiliation with religions that discourage alcohol use has a protective effect against hazardous drinking among women in general population studies [130,172], this relationship was not evident in a study cited in the current review and religiosity was not protective in a study using data from the CHLEW published after May 2017 [173]. It would be helpful to better understand the effects of religion and religiosity on AOD use among SMW as this may be a key influence on substance use, especially in conservative regions of the world.…”
Section: Gaps In Research On Aod Use Among Smwmentioning
confidence: 99%